Two Cases of Heerfordt’s Syndrome: A Rare Manifestation of Sarcoidosis - Keishi Fujiwara; Yasushi Furuta; Satoshi Fukuda (Case Reports in Otolaryngology)
Heerfordt’s syndrome is a rare manifestation of sarcoidosis characterized by the presence of facial nerve palsy, parotid gland enlargement, anterior uveitis, and low grade fever. Two cases of Heerfordt’s syndrome and a literature review are presented. Case  1. A 53-year-old man presented with swelling of his right eyelid, right facial nerve palsy, and swelling of his right parotid gland. A biopsy specimen from the swollen eyelid indicated sarcoidosis and he was diagnosed with incomplete Heerfordt’s syndrome based on the absence of uveitis. His symptoms were improved by corticosteroid therapy. Case  2. A 55-year-old woman presented with left facial nerve palsy, bilateral hearing loss, and swelling of her bilateral parotid glands. She had been previously diagnosed with uveitis and bilateral hilar lymphadenopathy. Although no histological confirmation was performed, she was diagnosed with complete Heerfordt’s syndrome on the basis of her clinical symptoms. Swelling of the bilateral parotid glands and left facial nerve palsy were improved immediately by corticosteroid therapy. Sarcoidosis is a relatively uncommon disease for the otolaryngologist. However, the otolaryngologist may encounter Heerfordt’s syndrome as this syndrome presents with facial nerve palsy and swelling of the parotid gland. Therefore, we otolaryngologists should diagnose and treat Heerfordt’s syndrome appropriately in cooperation with pneumologists and ophthalmologists.